Cultural Variations in Conceptual Metaphors of Love in English and Vietnamese - Phuong, Ngo Dinh; Anh, Nguyen Thi Kim (VNU Journal of Foreign Studies; Vol 32 No 2, 2016)
Abstract : One central issue in cognitive linguistics that has received interest from researchers in recent years is the conceptual metaphor. This article focuses on cultural variations in conceptual metaphors of love between English and Vietnamese. In order to enhance English teaching and learning, we would like to analyze different possibilities of cultural variations from a cognitive perspective and propose several explanations for those issues. Keywords:   Conceptual metaphor, metaphor of love, cultural variations.